2015
DOI: 10.1038/ki.2015.196
|View full text |Cite
|
Sign up to set email alerts
|

IL-3 contributes to development of lupus nephritis in MRL/Ipr mice

Abstract: MRL/lpr mice develop a spontaneous autoimmune disease that closely resembles human systemic lupus erythematosus (SLE) with DNA autoantibodies, hypergammaglobulinemia, immune complex glomerulonephritis, and systemic vasculitis. Little is known about the role of IL-3 in SLE. In order to study this we analyzed the expression of IL-3 in murine lupus and determined whether blockade of IL-3 with a monoclonal antibody or injection of recombinant IL-3 affects lupus nephritis in MRL/lpr mice. During disease progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 59 publications
4
31
0
1
Order By: Relevance
“…Moreover, i.p. injection of IL-3 may also induce peripheral activation of leukocytes, thus facilitating their transendothelial migration, and could increase the survival of T and B cells, as shown previously in mice with lupus nephritis (23). Interestingly, injection of IL-3 mainly increased in the infiltration of CD4 + and CD8 + T cells, indicating that migration of T cells into the CNS is, to a large degree, dependent on the presence of IL-3, while migration of monocytes into the CNS is less dependent on IL-3.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Moreover, i.p. injection of IL-3 may also induce peripheral activation of leukocytes, thus facilitating their transendothelial migration, and could increase the survival of T and B cells, as shown previously in mice with lupus nephritis (23). Interestingly, injection of IL-3 mainly increased in the infiltration of CD4 + and CD8 + T cells, indicating that migration of T cells into the CNS is, to a large degree, dependent on the presence of IL-3, while migration of monocytes into the CNS is less dependent on IL-3.…”
Section: Discussionsupporting
confidence: 55%
“…IL-3 induces activation and/or increases the survival of various target cells, including mast cells, basophils, monocytes, DCs, B cells, T cells, and endothelial cells (14)(15)(16)(17)(18)(19)(20)(21). An important role of IL-3 in inflammation and autoimmunity was recently shown in a model of sepsis (9), as well as in models of arthritis and lupus nephritis (22,23). IL-3 increases the release of monocytes and neutrophils from the BM, activates monocytes and BM cells to release proinflammatory cytokines, has antiapoptotic effects on various leukocytes, and activates endothelial cells to upregulate E-and P-selectin (9,(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…We find that the IL-3 and Wnt signatures emerge as the most discriminating between SLE and control donors ( Supplementary Figure 2e). Notably, previous studies support a role for IL-3 in SLE in connection with B cells: IL-3 is a growth factor for B cells [36], serum levels of IL-3 have been observed to be increased in SLE patients vs healthy controls [37], and a recent study in a lupus nephritis mouse model found that IL-3 blockade ameliorated disease symptoms and notably reduced splenic B-cell counts [38].…”
Section: Distinct Signature Modules Drive Transcriptional Variation Imentioning
confidence: 90%
“…In the MRL/lpr murine lupus model, IL-3 administration exacerbated nephritis, and IL-3 blockade alleviated disease and decreased autoantibody production. 2 Plasma levels of IL-3 increased during disease progression in these mice, and IL-3 was produced by CD4 + T cells derived from the spleen and bone marrow, and by CD8 + T cells derived from the spleen. Recently, a therapeutic monoclonal antibody that neutralises IL-3 and also depletes CD123 + cells was shown to decrease cell types (plasmacytoid dendritic cells [pDCs] and basophils) and cytokines implicated in the pathogenesis of SLE, including type I and III IFNs, in primary cells from SLE patients.…”
Section: Introductionmentioning
confidence: 87%
“…Recent studies of murine lupus have more directly identified a role for IL‐3. In the MRL/ lpr murine lupus model, IL‐3 administration exacerbated nephritis, and IL‐3 blockade alleviated disease and decreased autoantibody production . Plasma levels of IL‐3 increased during disease progression in these mice, and IL‐3 was produced by CD4 + T cells derived from the spleen and bone marrow, and by CD8 + T cells derived from the spleen.…”
Section: Introductionmentioning
confidence: 98%